Eksistensi ASEAN sebagai Organisasi Regional pada Aspek Sosial Budaya Melalui Program Student Mobility - Eldaa, Monica Roza Nandelia (Sahabat Publikasi, 2024)
The study of international relations originated in Great Britain precisely in the early 20th century in Wales, when a group of experts in philosophy and international law in Great Britain agreed on the need to study relations between nations. At first, international relations focused more on the study of war and peace in nation-state relations. However, beginning in the 1970s and 1980s the study of international relations expanded to a wider range of studies. International relations develop on non-political issues, such as economics, security, law, culture, technology, and so on. Any perspective in an approach that views international relations as not only state-oriented would say that other entities such as International Organizations also have an important role. One of the International Organizations at the Regional Level is The Association of Southeast Asian Nations (ASEAN). ASEAN has 3 pillars, namely Political-Security, Economic and Socio-Cultural.2 International Relations are inseparable from globalization. Globalization encourages countries indirectly to cooperate with each other in order to meet their national interests and respond to the phenomena that exist along with globalization. One form of cooperation is international cooperation. International organizations have several forms, one of which is in the Regional scope. ASEAN as one of the Regional Organizations collaborates in the field of Socio-Culture through the Student Mobility program.